Tripchlorolide improves age-associated cognitive deficits by reversing hippocampal synaptic plasticity impairment and NMDA receptor dysfunction in SAMP8 mice - Lin, Nan; Pan, Xiao-dong; Chen, Ai-qin; Zhu, Yuan-gui; Wu, Ming; Zhang, Jing; Chen, Xiao-chun (Behavioural brain research, 2014)
•A novel extract of natural herbal, tripchlorolide has anti-dementia action.•Long-term T4 treatment prevents learning and memory loss in aged SAMP8 mice.•T4 ameliorates hippocampal LTP in aged SAMP8 mice.•T4 alleviates synaptic plasticity dysfunction of the hippocampus.•T4 intensified the signal pathway of CaMKII-CREB-BDNF in SAMP8 mice. Deficits in cognition and performance accompanying age-related neurodegenerative diseases such as Alzheimer's disease (AD) are closely associated with the impairment of synaptic plasticity. Here, using a mouse model of senescence-accelerated P8 (SAMP8), we reported the role of tripchlorolide (T4), an extract of the natural herb Tripterygium wilfordii Hook F, in improving cognitive deficits and promoting the long-term potentiation (LTP) of hippocampal slices via the N-methyl-d-aspartate receptor (NMDAR)-dependent signaling pathway. Our results demonstrated that chronic administration of T4 at low doses (0.25, 1.0, or 4.0μg/kg per day, injected intraperitoneally for 75 days) significantly improved learning and memory function in aged SAMP8 mice, as indicated by a chain of behavioral tests including the Y-maze and Morris water maze. Additionally, T4 reversed the impaired LTP in hippocampal CA1 regions of SAMP8 mice in a dose-dependent manner. Moreover, it upregulated the levels of phospho-NMDAR1, postsynaptic density-95 (PSD-95), phospho-calcium-calmodulin dependent kinase II (CaMKII), phospho-CREB and brain derived neurotrophic factor (BDNF) in the hippocampus. This indicates that T4 prevents the impairment of NMDAR-mediated synaptic plasticity-related signal molecules. At optimal doses, T4 did not show significant side-effects on blood counts, blood biochemical measures, or survival of the mice. This novel mechanism in reversing age-related synaptic dysfunction and NMDAR functional deficits suggests that T4 can halt the manifestation of a key early-stage event in AD. With the consideration of SAMP8 mice as a model to develop therapeutic interventions for AD, our findings provide new insight into the clinical application of tripchlorolide in AD treatment.